2017
DOI: 10.1177/0886260517719542
|View full text |Cite
|
Sign up to set email alerts
|

Animal Maltreatment as a Risk Marker of More Frequent and Severe Forms of Intimate Partner Violence

Abstract: Although there is a growing body of literature documenting the co-occurrence of animal abuse and intimate partner violence (IPV), only a few studies have examined the relationship between animal maltreatment, types of IPV, and abuse severity. The results of those studies have been inconclusive and in some cases even contradictory. The current study contributes new findings to that specific segment of the literature and sheds some light on the inconsistent findings in previous studies. Data were gathered from 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 30 publications
(61 reference statements)
5
53
1
Order By: Relevance
“…They noted, however, that this finding may be a function of the sample, nearly half of which was comprised of Mexican immigrants; Mexican‐born men were nearly four times less likely to harm an animal than non‐Hispanic U.S.‐born men. In contrast, using a sample of women receiving services from domestic violence shelters in Canada, Barrett, Fitzgerald, Stevenson, and Cheung () found that women whose pets were more frequently and severely abused by their partners reported experiencing significantly higher rates of physical, sexual, and psychological abuse by their partners compared with abused women who reported little or no maltreatment of their pets by their partner.…”
Section: “The Link” Between Animal Maltreatment and Interpersonal Viomentioning
confidence: 98%
“…They noted, however, that this finding may be a function of the sample, nearly half of which was comprised of Mexican immigrants; Mexican‐born men were nearly four times less likely to harm an animal than non‐Hispanic U.S.‐born men. In contrast, using a sample of women receiving services from domestic violence shelters in Canada, Barrett, Fitzgerald, Stevenson, and Cheung () found that women whose pets were more frequently and severely abused by their partners reported experiencing significantly higher rates of physical, sexual, and psychological abuse by their partners compared with abused women who reported little or no maltreatment of their pets by their partner.…”
Section: “The Link” Between Animal Maltreatment and Interpersonal Viomentioning
confidence: 98%
“…Animal cruelty by domestic partners and other family members was more prevalent in violent families compared to those without domestic violence [ 10 ]. A Canadian study indicated that women reporting violence to their animals tended to suffer abuse themselves with greater frequency and severity [ 14 ].…”
Section: Animal Cruelty and Neighborhood Conditionsmentioning
confidence: 99%
“…Therefore, many victims of domestic violence delay leaving an abusive relationship because they have no safe place for their animals (Ascione et al 1997). A 2017 study showed that 56 percent of women in domestic violence shelters had delayed their escape out of fear for their animals and a desire to protect them (Barrett et al 2017).…”
Section: Domestic Violence and Animal Abusementioning
confidence: 99%